Nonaqueous electrolyte for lithium secondary battery and lithium secondary battery containing same
The nonaqueous electrolyte for lithium secondary batteries, incorporating a phosphonium salt-based ionic liquid with a propargyl group, addresses the challenges of flame retardancy and temperature-related performance issues by forming a rigid electrode coating, thereby enhancing stability and capacity retention.
Patent Information
- Application Number
- JP2024556762
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-03-30
- Filing Date
- 2023-03-31
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2043-03-31
AI Technical Summary
Existing lithium-ion batteries face challenges with flame retardancy and performance stability in high and low temperature environments due to the volatility of organic solvents and side reactions with electrodes.
A nonaqueous electrolyte for lithium secondary batteries is developed, comprising a lithium salt, a nonaqueous organic solvent, and a phosphonium salt-based ionic liquid with a propargyl group, which forms a rigid coating on electrodes, enhancing flame retardancy and reducing resistance at low temperatures.
The proposed electrolyte improves flame retardancy, maintains capacity characteristics by minimizing resistance increase at low temperatures, and ensures excellent storage stability at high temperatures.
Smart Images

Figure 2025510856000001_ABST
Abstract
Description
[Technical field]
[0001] This application claims the benefit of priority based on Korean Patent Application No. 10-2022-0040774 filed on March 31, 2022 and Korean Patent Application No. 10-2023-0041707 filed on March 30, 2023, and all contents disclosed in the documents of said Korean patent applications are incorporated by reference into this specification.
[0002] The present invention relates to a non-aqueous electrolyte for lithium secondary batteries containing a phosphonium salt-based ionic liquid, and a lithium secondary battery containing the same. [Background technology]
[0003] As modern society becomes more and more dependent on electrical energy, the amount of electrical energy produced is increasing. To solve environmental problems that arise when producing electrical energy, renewable energy power generation is attracting attention as a next-generation power generation system. Since such renewable energy exhibits intermittent power generation characteristics, a large-capacity power storage device is essential to stably supply power. Among such power storage devices, lithium-ion batteries are attracting attention as devices that exhibit the highest energy density currently commercially available.
[0004] The lithium ion battery is mainly composed of a positive electrode made of a transition metal oxide containing lithium, a negative electrode capable of storing lithium, a non-aqueous electrolyte that serves as a medium for transmitting lithium ions, and a separator.
[0005] In particular, non-aqueous electrolytes are known to be components that have a significant effect on the stability and safety of batteries, and much research on them has been conducted.
[0006] In general, non-aqueous electrolytes have mainly been used as liquid electrolytes in which electrolyte salts are dissolved in organic solvents. However, such liquid electrolytes have the disadvantages that the volatility of the organic solvent is high in a high-temperature atmosphere, a large amount of gas is generated by a side reaction with the electrodes, and the stability is low due to combustion caused by the temperature rise of the battery itself. Furthermore, the performance is deteriorated due to the increase in resistance at the interface between the electrodes and the non-aqueous electrolyte in a low-temperature atmosphere. Therefore, there is a demand for the development of a lithium secondary battery that is flame retardant and has improved performance in high and low temperature environments. Summary of the Invention [Problem to be solved by the invention]
[0007] The present invention has been made to solve the above problems, and has an object to provide a non-aqueous electrolyte for lithium secondary batteries that contains a phosphonium salt-based ionic liquid.
[0008] Another object of the present invention is to provide a lithium secondary battery that contains the nonaqueous electrolyte solution for a lithium secondary battery, thereby improving flame retardancy, output characteristics in a low-temperature atmosphere, and stability and storage characteristics in a high-temperature atmosphere. [Means for solving the problem]
[0009] In order to achieve the above object, one embodiment of the present invention comprises: The present invention provides a non-aqueous electrolyte solution for a lithium secondary battery, comprising a lithium salt, a non-aqueous organic solvent, and an ionic liquid represented by the following chemical formula 1:
[0010] [ka]
[0011] In the above Chemical Formula 1, R is an alkylene group having 1 to 5 carbon atoms; R1 to R3 each independently represent an alkyl group having 1 to 8 carbon atoms or an aryl group having 6 to 12 carbon atoms; X- is BF4 - , PF6 - , ClO4 - , PO2F2 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , SO3CF3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , B(C2O4)2 - , and BF2(C2O4) - and at least one anion selected from the group consisting of:
[0012] Another embodiment of the present invention comprises: The present invention provides a lithium secondary battery comprising a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and a nonaqueous electrolyte, the nonaqueous electrolyte comprising the nonaqueous electrolyte for lithium secondary batteries of the present invention. Effect of the Invention
[0013] The phosphonium salt-based ionic liquid represented by Chemical Formula 1 contained in the non-aqueous electrolyte of the present invention contains a propargyl group in its structure, and thus can form a low-resistance, robust coating on the surface of the electrode through an oxidation / reduction reaction. Therefore, when the non-aqueous electrolyte of the present invention containing the phosphonium salt-based ionic liquid represented by Chemical Formula 1 is used, it is possible to improve flame retardancy and minimize the increase in resistance at low temperatures to improve capacity characteristics, thereby realizing a lithium secondary battery that can ensure excellent high-temperature storage stability.
[0014] The following drawings attached to this specification illustrate preferred embodiments of the present invention and, together with the above-mentioned content of the invention, serve to further understand the technical ideas of the present invention. Therefore, the present invention should not be interpreted as being limited only to the matters described in the drawings. [Brief description of the drawings]
[0015] [Figure 1] 13 is a graph showing evaluation results of a thickness increase rate during high-temperature storage of a lithium secondary battery in Experimental Example 2. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] The present invention will now be described in more detail. The terms and words used in this specification and the claims should not be interpreted in a limited manner to their ordinary or dictionary meanings, but should be interpreted in a manner that is consistent with the technical idea of the present invention, based on the principle that the inventors can appropriately define the concepts of terms in order to best describe their invention.
[0017] Nonaqueous electrolyte for lithium secondary batteries Specifically, one embodiment of the present invention comprises: The present invention provides a non-aqueous electrolyte solution for a lithium secondary battery, comprising a lithium salt, a non-aqueous organic solvent, and an ionic liquid represented by the following chemical formula 1:
[0018] [ka]
[0019] In the above Chemical Formula 1, R is an alkylene group having 1 to 5 carbon atoms; R1 to R3 each independently represent an alkyl group having 1 to 8 carbon atoms or an aryl group having 6 to 12 carbon atoms; X - is BF4 - , PF6 - , ClO4 - , PO2F2 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , SO3CF3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N -, CF3CF2SO3 - , CF3CF2(CF3)2CO - , B(C2O4)2 - , and BF2(C2O4) - and at least one anion selected from the group consisting of:
[0020] (1) Lithium salt First, the lithium salt will be described as follows. As the lithium salt, any salt commonly used in non-aqueous electrolytes for lithium secondary batteries can be used without limitation. For example, the cation is Li + The anion is F. - , Cl - , Br - , I - , NO3 - , N(CN)2 - , BF4 - , ClO4 - , B 10 Cl 10 - , AlCl4 - , AlO4 - , PF6 - , CF3SO3 - , CH3CO2 - , CF3CO2 - , AsF6 - , SbF6 - , CH3SO3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , BF2C2O4 - , BC4O8 - , PF4C2O4 - , PF2C4O8 - , (CF3)2PF4 - , (CF3)3PF3 - , (CF3)4PF2 - , (CF3)5PF - , (CF3)6P - , C4F9SO3 - , CF3CF2SO3 - , CF3CF2(CF3)2CO -, (CF3SO2)2CH - , CF3(CF2)7SO3 - , and SCN - The composition may include at least one selected from the group consisting of:
[0021] Specifically, the lithium salt is LiCl, LiBr, LiI, LiBF4, LiClO4, LiB 10 Cl 10 The lithium salt may include a single substance or a mixture of two or more substances selected from the group consisting of LiAlCl4, LiAlO4, LiPF6, LiCF3SO3, LiCH3CO2, LiCF3CO2, LiAsF6, LiSbF6, LiCH3SO3, LiFSI (lithium bis(fluorosulfonyl)imide, LiN(SO2F)2), LiBETI (lithium bis(pentafluoroethanesulfonyl)imide, LiN(SO2CF2CF3)2, and LiTFSI (lithium bis(trifluoromethanesulfonyl)imide, LiN(SO2CF3)2). In addition to the above-mentioned lithium salts, lithium salts commonly used in electrolytes for lithium secondary batteries may be used without limitation. Specifically, the lithium salt may include LiPF6.
[0022] The lithium salt may be appropriately changed within a range that is generally usable, but in order to obtain an optimal effect of forming a coating for preventing corrosion of the electrode surface, it may be contained in the electrolyte at a concentration of 0.8 M to 3.0 M, specifically, at a concentration of 1.0 M to 3.0 M. When the concentration of the lithium salt satisfies the above range, the viscosity of the nonaqueous electrolyte can be controlled so as to realize optimal impregnation, and the mobility of lithium ions can be improved, thereby obtaining an effect of improving the capacity characteristics and cycle characteristics of the lithium secondary battery.
[0023] (2) Non-aqueous organic solvent The non-aqueous organic solvent is described as follows. As the non-aqueous organic solvent, various organic solvents commonly used in non-aqueous electrolytes can be used without limitation, and there is no limitation on the type of the organic solvent as long as it can minimize decomposition due to oxidation reaction during the charge / discharge process of the secondary battery and can exhibit the desired properties together with the additives.
[0024] Specifically, the non-aqueous organic solvent may include a cyclic carbonate organic solvent, a linear carbonate organic solvent, a linear ester organic solvent, or a mixture thereof.
[0025] The cyclic carbonate organic solvent is a high-viscosity organic solvent that has a high dielectric constant and effectively dissociates the lithium salt in the non-aqueous electrolyte solution. Specific examples of the cyclic carbonate organic solvent include at least one organic solvent selected from the group consisting of ethylene carbonate (EC), propylene carbonate (PC), 1,2-butylene carbonate, 2,3-butylene carbonate, 1,2-pentylene carbonate, 2,3-pentylene carbonate, and vinylene carbonate, and among these, ethylene carbonate may be included.
[0026] The linear carbonate organic solvent is an organic solvent having low viscosity and low dielectric constant, and specific examples thereof may include at least one organic solvent selected from the group consisting of dimethyl carbonate (DMC), diethyl carbonate (DEC), dipropyl carbonate, ethyl methyl carbonate (EMC), methyl propyl carbonate, and ethyl propyl carbonate, and specifically may include ethyl methyl carbonate (EMC).
[0027] The linear ester organic solvent is a solvent that is relatively more stable at high temperatures and high voltages than cyclic carbonate organic solvents, and can improve the drawback of cyclic carbonate organic solvents that cause gas generation during high voltage operation, while also achieving high ionic conductivity.
[0028] Specific examples of the linear ester organic solvent include at least one selected from the group consisting of methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, and butyl propionate, and specifically, at least one of ethyl propionate and propyl propionate.
[0029] Furthermore, the non-aqueous electrolyte of the present invention may further contain a cyclic ester organic solvent, if necessary. The cyclic ester organic solvent may contain at least one selected from the group consisting of γ-butyrolactone, γ-valerolactone, γ-caprolactone, σ-valerolactone, and ε-caprolactone.
[0030] Meanwhile, the remainder of the non-aqueous electrolyte solution of the present invention, excluding the lithium salt and the compound represented by Chemical Formula 1 as an additive, may be a non-aqueous organic solvent unless otherwise specified.
[0031] (3) Ionic liquid represented by chemical formula 1 The nonaqueous electrolyte for a lithium secondary battery of the present invention may contain an ionic liquid represented by the following chemical formula 1 as an additive.
[0032] [ka]
[0033] In the above Chemical Formula 1, R is an alkylene group having 1 to 5 carbon atoms; R1 to R3 each independently represent an alkyl group having 1 to 8 carbon atoms or an aryl group having 6 to 12 carbon atoms; X - is BF4 - , PF6 - , ClO4 - , PO2F2 - , CF3SO3 - , CH3CO2 - , CF3CO2 -, SO3CF3 - , (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , B(C2O4)2 - , and BF2(C2O4) - and at least one anion selected from the group consisting of:
[0034] The phosphonium salt-based ionic liquid represented by Chemical Formula 1 contains a propargyl group in its structure, and therefore, compared to phosphonium salt-based ionic liquids containing double bonds, it has stable oxidation / reduction reactivity, which can further promote the reaction of additives for forming a coating, such as ethylene carbonate (EC), vinylene carbonate (VC), or vinyl ethylene carbonate (VEC), and can form a robust coating in the form of copolymerization with low resistance on the surface of the electrode, thereby further enhancing the durability of the coating. In addition, the phosphonium salt-based ionic liquid represented by Chemical Formula 1 is a non-volatile compound and has higher flame retardancy than organic solvents, such as ethylene carbonate (EC), which are included as the main component of conventional non-aqueous electrolytes, and therefore can improve the flame retardancy of a lithium secondary battery under a high-temperature atmosphere and reduce the possibility of ignition. Thus, when the non-aqueous electrolyte of the present invention containing the phosphonium salt-based ionic liquid represented by Chemical Formula 1 is applied, it is possible to realize a lithium secondary battery having improved low-temperature output characteristics, stability and storage characteristics under a high-temperature atmosphere by improving flame retardancy and minimizing the increase in resistance under a low-temperature atmosphere.
[0035] Specifically, in the above Chemical Formula 1, R is an alkylene group having 1 to 3 carbon atoms, R1 to R3 are each independently an alkyl group having 1 to 5 carbon atoms or a phenyl group, and X - is BF4 - , PF6 - , ClO4 - , PO2F2 - , CF3SO3 - , SO3CF3 -, (CF3CF2SO2)2N - , (CF3SO2)2N - , (FSO2)2N - , CF3CF2SO3 - , CF3CF2(CF3)2CO - , and BF2(C2O4) - The anion may be at least one of the following: In addition, in the above chemical formula 1, R1 to R3 may each independently be a methyl group, an ethyl group, or a phenyl group.
[0036] More specifically, the ionic liquid represented by Chemical Formula 1 may be at least one of the compounds represented by Chemical Formulas 1-1 to 1-4 below.
[0037] [ka]
[0038] [ka]
[0039] [ka]
[0040] [ka]
[0041] The ionic liquid represented by Chemical Formula 1 may be included in an amount of 0.3 wt % to 50 wt % based on the total weight of the non-aqueous electrolyte solution. When the content of the ionic liquid represented by Chemical Formula 1 satisfies the above range, a stable passivation film with low resistance is formed on the surfaces of the positive and negative electrodes, ensuring safe high and low temperature capacity characteristics, and enhancing flame retardancy, thereby further improving the performance of the lithium secondary battery under high and low temperature atmospheres.
[0042] Specifically, the ionic liquid represented by Chemical Formula 1 may be included in an amount of 0.5% by weight to 30% by weight, preferably 0.5% by weight to 20% by weight, based on the total weight of the non-aqueous electrolyte.
[0043] (4) Other additives In addition, the nonaqueous electrolyte for a lithium secondary battery of the present invention may further contain other additives as necessary in order to prevent the collapse of the negative electrode caused by decomposition of the nonaqueous electrolyte in a high-output environment, and to further improve low-temperature high-rate discharge characteristics, high-temperature stability, prevention of overcharging, and effect of suppressing battery expansion at high temperatures.
[0044] Representative examples of such other additives may include at least one selected from the group consisting of cyclic carbonate-based compounds, halogen-substituted carbonate-based compounds, sultone-based compounds, sulfate-based compounds, phosphate-based compounds, borate-based compounds, nitrile-based compounds, benzene-based compounds, amine-based compounds, silane-based compounds, and lithium salt-based compounds.
[0045] Examples of the cyclic carbonate compounds include vinylene carbonate (VC) and vinyl ethylene carbonate. The halogen-substituted carbonate compounds include fluoroethylene carbonate (FEC).
[0046] The sultone compound includes at least one compound selected from the group consisting of 1,3-propane sultone (PS), 1,4-butane sultone, ethene sultone, 1,3-propene sultone (PRS), 1,4-butene sultone, and 1-methyl-1,3-propene sultone.
[0047] The sulfate compounds include ethylene sulfate (Esa), trimethylene sulfate (TMS), and methyl trimethylene sulfate (MTMS).
[0048] The phosphate-based compound may be one or more compounds selected from the group consisting of lithium difluoro(bisoxalato)phosphate, lithium difluorophosphate, tris(trimethylsilyl)phosphate, tris(2,2,2-trifluoroethyl)phosphate, and tris(trifluoroethyl)phosphate. Examples of the borate-based compounds include tetraphenylborate and lithium oxalyl difluoroborate.
[0049] The nitrile compound may be at least one compound selected from the group consisting of succinonitrile, adiponitrile, acetonitrile, propionitrile, butyronitrile, valeronitrile, caprylonitrile, heptanenitrile, cyclopentanecarbonitrile, cyclohexanecarbonitrile, 2-fluorobenzonitrile, 4-fluorobenzonitrile, difluorobenzonitrile, trifluorobenzonitrile, phenylacetonitrile, 2-fluorophenylacetonitrile, and 4-fluorophenylacetonitrile.
[0050] The benzene-based compound may be fluorobenzene, the amine-based compound may be triethanolamine or ethylenediamine, and the silane-based compound may be tetravinylsilane.
[0051] The lithium salt compound is a compound different from the lithium salt contained in the nonaqueous electrolyte, and may be one or more compounds selected from the group consisting of LiPO2F2, LiODFB, LiBOB (lithium bis(oxalato)borate (LiB(C2O4)2), and LiBF4.
[0052] Among these other additives, when vinylene carbonate, vinyl ethylene carbonate, or succinonitrile is included, a stronger SEI film can be formed on the surface of the negative electrode during the initial activation process of the secondary battery.
[0053] Meanwhile, the other additives may be used in combination of two or more kinds, and may be included in an amount of 50% by weight or less, specifically 0.01% by weight to 10% by weight, and preferably 0.05% by weight to 5.0% by weight, based on the total weight of the non-aqueous electrolyte. If the content of the other additives is less than 0.01% by weight, the effect of improving the low-temperature output and the high-temperature storage characteristics and high-temperature life characteristics of the battery is insignificant, and if the content of the other additives is more than 50% by weight, excessive side reactions may occur in the electrolyte during charging and discharging of the battery. In particular, when the SEI film forming additive is added in excess, it cannot be sufficiently decomposed at high temperatures and may exist in the electrolyte at room temperature in the form of an unreacted substance or precipitate. This may cause side reactions that reduce the life or resistance characteristics of the secondary battery.
[0054] Lithium secondary battery In addition, another embodiment of the present invention provides a lithium secondary battery including a positive electrode, a negative electrode, a separator interposed between the positive electrode and the negative electrode, and the nonaqueous electrolyte of the present invention.
[0055] The lithium secondary battery of the present invention may be manufactured by forming an electrode assembly in which a positive electrode, a negative electrode, and a separator are sequentially stacked between the positive electrode and the negative electrode, housing the electrode assembly in a battery case, and then injecting the nonaqueous electrolyte of the present invention into the battery case.
[0056] The method for manufacturing the lithium secondary battery of the present invention may be applied by a conventional method well known in the art, and will be described in detail below.
[0057] (1) Positive electrode The positive electrode according to the present invention may include a positive electrode active material layer containing a positive electrode active material. Optionally, the positive electrode active material layer may further include a conductive material and / or a binder.
[0058] The positive electrode active material is a compound capable of reversible intercalation and deintercalation of lithium. Specifically, it may include a lithium composite metal oxide represented by the following Chemical Formula 2, which contains at least one metal selected from the group consisting of nickel (Ni), cobalt (Co), manganese (Mn), iron (Fe), and aluminum (Al) and lithium.
[0059] [Chemical Formula 2] Li 1+a Ni x Co y M 1 z M 2 w O2
[0060] In Chemical Formula 2, M 1 is Mn, Al, or a combination thereof, M 2 is at least one selected from the group consisting of Al, Zr, W, Ti, Mg, Ca, and Sr, and 0 ≦ a ≦ 0.5, 0 < x ≦ 1.0, 0 < y ≦ 0.4, 0 < z ≦ 0.4, 0 ≦ w ≦ 0.1.
[0061] 1 + a represents the atomic fraction of lithium in the lithium transition metal oxide. At this time, 0 ≦ a ≦ 0.5, preferably 0 ≦ a ≦ 0.2, more preferably 0 ≦ a ≦ 0.1 may be satisfied.
[0062] x represents the atomic fraction of nickel among all transition metal elements in the lithium transition metal oxide, and 0 < x ≦ 1.0. Specifically, 0.55 < x < 1.0, more specifically 0.6 ≦ x ≦ 0.98, and even more specifically 0.6 ≦ x ≦ 0.95 may be satisfied.
[0063] Said y represents the atomic fraction of cobalt among all transition metal elements in the lithium transition metal oxide, where 0 < y ≦ 0.4, specifically 0 < y ≦ 0.3, and more specifically 0.05 ≦ y ≦ 0.3 may also be applicable.
[0064] Said z represents the atomic fraction of element M among all transition metal elements in the lithium transition metal oxide, where 0 < z ≦ 0.4, preferably 0 < z ≦ 0.3, and more preferably 0.01 ≦ z ≦ 0.3 may also be applicable. 1
[0065] Said w represents the atomic fraction of element M among all transition metal elements in the lithium transition metal oxide, where 0 < w ≦ 0.1, preferably 0 < w ≦ 0.05, and more preferably 0 < w ≦ 0.02. 2
[0066]
[0067] Specifically, in order to realize a high-capacity battery, the cathode active material contains Li(Ni 0.6 Mn 0.2 Co 0.2 )O2, Li(Ni 0.7 Mn 0.15 Co 0.15 )O2, Li(Ni 0.7 Mn 0.2 Co 0.1 )O2, Li(Ni 0.8 Mn 0.1 Co 0.1 )O2, Li(Ni 0.8 Co 0.15 Al 0.05 )O2, Li(Ni 0.86 Mn 0.07 Co 0.05 Al 0.02 )O2, or may contain lithium composite transition metal oxides such as Li(Ni 0.90 Mn 0.05 Co 0.05 )O2.
[0067] In addition, the positive electrode active material of the present invention, together with the lithium composite metal oxide represented by the chemical formula 2, may be a lithium-manganese-based oxide (for example, LiMnO2, LiMn2O4, etc.), a lithium-cobalt-based oxide (for example, LiCoO2, etc.), a lithium-nickel-based oxide (for example, LiNiO2, etc.), a lithium-nickel-manganese-based oxide (for example, LiNi 1-Y Mn Y O2(0 < Y < 1), LiMn 2-z Ni z O4(0 < Z < 2), a lithium-nickel-cobalt-based oxide (for example, LiNi 1-Y1 Co Y1 O2(0 < Y1 < 1), a lithium-manganese-cobalt-based oxide (for example, LiCo 1-Y2 Mn Y2 O2(0 < Y2 < 1), LiMn 2-z1 Co z1 O4(0 < Z1 < 2), or Li(Ni p1 Co q1 Mn r2 )O4(0 < p1 < 2, 0 < q1 < 2, 0 < r2 < 2, p1 + q1 + r2 = 2), etc., may be used in combination.
[0068] The positive electrode active material may be contained in an amount of 80% by weight to 99% by weight, specifically 90% by weight to 99% by weight, based on the total weight of the solid content in the positive electrode slurry. At this time, when the content of the positive electrode active material is 80% by weight or less, the energy density may be low and the capacity may decrease.
[0069] Next, the conductive material is used to give conductivity to the electrode, and can be used without any particular limitation as long as it does not cause chemical changes in the battery that is constructed and has electronic conductivity.Specific examples include carbon powders such as carbon black, acetylene black (or denka black), ketjen black, channel black, furnace black, lamp black, and thermal black; graphite powders such as natural graphite, artificial graphite, and graphite with highly developed crystal structures; conductive fibers such as carbon fibers and metal fibers; conductive powders such as carbon fluoride powder, aluminum powder, and nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxides such as titanium oxide; conductive materials such as polyphenylene derivatives, and the like, and one or more of these may be used alone or in mixture. The conductive material may be contained in an amount of 0.1% by weight to 10% by weight, preferably 0.1% by weight to 5.0% by weight, based on the total weight of the positive electrode active material layer.
[0070] Secondly, the binder serves to improve adhesion between particles of the positive electrode active material and the adhesive strength between the positive electrode active material and the current collector. Examples of such binders include fluororesin-based binders including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders including styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, and styrene-isoprene rubber; cellulose-based binders including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders including polyvinyl alcohol; polyolefin-based binders including polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders, which may be used alone or in combination of two or more. The binder may be included in an amount of 0.1% by weight to 15% by weight, preferably 0.1% by weight to 10% by weight, based on the total weight of the positive electrode active material layer.
[0071] The positive electrode of the present invention may be manufactured by a method known in the art for manufacturing a positive electrode. For example, the positive electrode may be manufactured by a method of dissolving or dispersing a positive electrode active material, a binder, and / or a conductive material in a solvent to prepare a positive electrode slurry, which is then coated on a positive electrode current collector, and then dried and rolled to form an active material layer, or by a method of casting the positive electrode slurry on another support, peeling off the support, and laminating the resulting film on the positive electrode current collector.
[0072] The positive electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity, and may be, for example, stainless steel, aluminum, nickel, titanium, baked carbon, or aluminum or stainless steel surface-treated with carbon, nickel, titanium, silver, etc. The positive electrode current collector may generally have a thickness of 3 μm to 500 μm, and fine irregularities may be formed on the surface of the current collector to increase the adhesive strength of the positive electrode material. For example, it may be used in various forms such as a film, sheet, foil, net, porous body, foam, nonwoven fabric, etc.
[0073] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is not particularly limited as long as it can be adjusted to an appropriate viscosity of the positive electrode mixture in consideration of the coating thickness of the positive electrode mixture, production yield, workability, etc.
[0074] (2) Negative electrode Next, the negative electrode will be described. The negative electrode according to the present invention includes a negative electrode active material layer containing a negative electrode active material, and the negative electrode active material layer may further include a conductive material and / or a binder, as necessary.
[0075] The negative electrode active material may be any of various negative electrode active materials used in the art, such as a carbon-based negative electrode active material, a silicon-based negative electrode active material, or a mixture thereof.
[0076] According to an embodiment, the negative electrode active material may include a carbon-based negative electrode active material, and the carbon-based negative electrode active material may include various carbon-based negative electrode active materials used in the art, such as graphite-based materials such as natural graphite, artificial graphite, and Kish graphite; pyrolytic carbon, mesophase pitch based carbon fiber, meso-carbon microbeads, mesophase pitches, and high-temperature fired carbon such as petroleum or coal tar pitch derived cokes, soft carbon, hard carbon, etc. The shape of the carbon-based negative electrode active material is not particularly limited, and materials of various shapes such as amorphous, plate-like, flaky, spherical, or fibrous may be used.
[0077] Preferably, the negative electrode active material may be at least one carbon-based negative electrode active material selected from natural graphite and artificial graphite. In order to increase the adhesive strength with the current collector and suppress detachment of the active material, both natural graphite and artificial graphite may be used.
[0078] According to another embodiment, the negative electrode active material may be a combination of the carbon-based negative electrode active material and the silicon-based negative electrode active material. The silicon-based negative electrode active material is, for example, metal silicon (Si), silicon oxide (SiO x, where 0 < x < 2), silicon carbide (SiC), and Si-Y alloy (where Y is an element selected from the group consisting of alkali metals, alkaline earth metals, Group 13 elements, Group 14 elements, transition metals, rare earth elements, and combinations thereof, and is not Si) may be included. As the element Y, Mg, Ca, Sr, Ba, Ra, Sc, Y, Ti, Zr, Hf, Rf, V, Nb, Ta, Db (dubnium), Cr, Mo, W, Sg, Tc, Re, Bh, Fe, Pb, Ru, Os, Hs, Rh, Ir, Pd, Pt, Cu, Ag, Au, Zn, Cd, B, Al, Ga, Sn, In, Ti, Ge, P, As, Sb, Bi, S, Se, Te, Po, and combinations thereof may be selected.
[0079] Since the silicon-based negative electrode active material exhibits higher capacity characteristics than the carbon-based negative electrode active material, when further containing the silicon-based negative electrode active material, even more excellent capacity characteristics can be obtained. However, in the case of a negative electrode containing a silicon-based negative electrode active material, compared with a graphite negative electrode, the SEI film contains more oxygen (O)-rich components, and the SEI film containing oxygen-rich components tends to be further decomposed when a Lewis acid such as HF or PF5 exists in the electrolyte. Therefore, in the case of a negative electrode containing a silicon-based negative electrode active material, in order to maintain a stable SEI film, it is necessary to suppress the generation of Lewis acids such as HF and PF5 in the electrolyte or remove (or scavenge) the generated Lewis acids. Since the non-aqueous electrolyte according to the present invention contains an electrolyte additive capable of forming a stable film on the positive electrode and the negative electrode, it is possible to effectively suppress the decomposition of the SEI film when using a negative electrode containing a silicon-based active material.
[0080] On the other hand, the mixing ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material may be 3:97 to 99:1, preferably 5:95 to 15:85 by weight. When the mixing ratio of the silicon-based negative electrode active material and the carbon-based negative electrode active material satisfies the above range, while improving the capacity characteristics, the volume expansion of the silicon-based negative electrode active material can be suppressed, and excellent cycle performance can be ensured.
[0081] The negative electrode active material may be included in an amount of 80 wt % to 99 wt % based on the total weight of the negative electrode active material layer. When the content of the negative electrode active material is in the above range, excellent capacity characteristics and electrochemical characteristics can be obtained.
[0082] Next, the conductive material may be included to further improve the conductivity of the negative electrode active material layer, and is not particularly limited as long as it does not cause a chemical change in the battery and has conductivity. For example, the conductive material may be carbon powder such as carbon black, acetylene black (or denka black), ketjen black, channel black, furnace black, lamp black, or thermal black; graphite powder such as natural graphite, artificial graphite, or graphite with a highly developed crystal structure; conductive fiber such as carbon fiber or metal fiber; conductive powder such as carbon fluoride powder, aluminum powder, or nickel powder; conductive whiskers such as zinc oxide and potassium titanate; conductive metal oxide such as titanium oxide; conductive materials such as polyphenylene derivatives, etc. The conductive material may be added in an amount of 10% by weight or less, preferably 5% by weight or less, based on the total weight of the negative electrode active material layer.
[0083] The binder is a component that aids in bonding between the conductive material, active material, and current collector, and examples thereof include fluororesin-based binders including polyvinylidene fluoride (PVDF) or polytetrafluoroethylene (PTFE); rubber-based binders including styrene butadiene rubber (SBR), acrylonitrile-butadiene rubber, and styrene-isoprene rubber; cellulose-based binders including carboxyl methyl cellulose (CMC), starch, hydroxypropyl cellulose, and regenerated cellulose; polyalcohol-based binders including polyvinyl alcohol; polyolefin-based binders including polyethylene and polypropylene; polyimide-based binders; polyester-based binders; and silane-based binders. The binder may be contained in an amount of usually 0.1% by weight to 15% by weight, preferably 0.1% by weight to 10% by weight, based on the total weight of the negative electrode active material layer.
[0084] The negative electrode may be manufactured by a method for manufacturing a negative electrode well known in the art. For example, the negative electrode may be manufactured by applying a negative electrode slurry, which is prepared by dissolving or dispersing a negative electrode active material and, optionally, a binder and a conductive material in a solvent, onto a negative electrode current collector, rolling and drying the slurry to form an active material layer, or by casting the negative electrode slurry onto another support, peeling off the support, and laminating the resulting film onto the negative electrode current collector.
[0085] The negative electrode current collector is not particularly limited as long as it does not cause a chemical change in the battery and has high conductivity, and may be, for example, copper, stainless steel, aluminum, nickel, titanium, baked carbon, copper or stainless steel surface-treated with carbon, nickel, titanium, silver, or aluminum-cadmium alloy. The negative electrode current collector may generally have a thickness of 3 μm to 500 μm, and may have fine irregularities formed on the surface of the current collector to strengthen the binding force of the negative electrode active material, as in the case of the positive electrode current collector. For example, the negative electrode current collector may be used in various forms such as a film, sheet, foil, net, porous body, foam, or nonwoven fabric.
[0086] The solvent may be a solvent commonly used in the art, such as dimethyl sulfoxide (DMSO), isopropyl alcohol, N-methylpyrrolidone (NMP), acetone, water, etc., and one or more of these may be used alone or in combination. The amount of the solvent used is not particularly limited as long as it can be adjusted to an appropriate viscosity for the negative electrode slurry in consideration of the coating thickness of the negative electrode composite, production yield, workability, etc.
[0087] (3) Separator The separator included in the lithium secondary battery of the present invention may be a commonly used conventional porous polymer film, for example, a porous polymer film made of a polyolefin polymer such as an ethylene homopolymer, a propylene homopolymer, an ethylene / butene copolymer, an ethylene / hexene copolymer, or an ethylene / methacrylate copolymer, either alone or in a laminated state, or a conventional porous nonwoven fabric, for example, a nonwoven fabric made of a high melting point glass fiber, a polyethylene terephthalate fiber, or the like, but is not limited thereto.
[0088] The external shape of the lithium secondary battery of the present invention is not particularly limited, and may be a cylindrical shape using a can, a square shape, a pouch shape, a coin shape, or the like.
[0089] [Example] Example 1. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:70 to a concentration of 1.0 M, and then 0.5 wt % of the compound represented by Chemical Formula 1-1 and other additives such as 1.0 wt % vinylene carbonate, 1.0 wt % 1,3-propane sultone, and 1.0 wt % ethylene sulfate were added to prepare a non-aqueous electrolyte.
[0090] (Secondary battery manufacturing) N-methyl-2-pyrrolidone (NMP) is used as the positive electrode active material (Li(Ni 0.86 Mn 0.07 Co 0.05 Al 0.02 A cathode slurry (solid content: 50 wt%) was prepared by adding 100% ethylenediaminetetraacetate (Et2O2), a conductive material (carbon black), and a binder (polyvinylidene fluoride) in a weight ratio of 97.5:1:1.5. The cathode slurry was applied to a 12 μm-thick aluminum (Al) thin film, which was a cathode current collector, and dried, followed by roll pressing to prepare a cathode.
[0091] Anode active material (graphite), binder (SBR-CMC), and conductive material (carbon black) were mixed in a weight ratio of 95:3.5:1.5 with water as a solvent to prepare anode slurry (solid content: 60 wt%). The anode slurry was applied to a copper (Cu) thin film as an anode current collector with a thickness of 6 μm, dried, and then roll pressed to prepare an anode.
[0092] The positive electrode, a polyolefin-based porous separator coated with inorganic particles (Al2O3), and a negative electrode were sequentially stacked to prepare an electrode assembly, which was then placed in a pouch-type battery case, and the non-aqueous electrolyte for lithium secondary batteries was injected to prepare a pouch-type lithium secondary battery having a driving voltage of 4.45 V or more.
[0093] Example 2. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:70 to a concentration of 1.0 M, and then 2.0 wt % of the compound represented by Chemical Formula 1-1 and other additives such as 1.0 wt % vinylene carbonate, 1.0 wt % 1,3-propane sultone, and 1.0 wt % ethylene sulfate were added to prepare a non-aqueous electrolyte.
[0094] (Secondary battery manufacturing) A pouch-type lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared above was injected.
[0095] Example 3. (Production of non-aqueous electrolyte) LiPF6 was dissolved in a non-aqueous organic solvent in which ethylene carbonate (EC) and ethyl methyl carbonate (EMC) were mixed in a volume ratio of 30:70 to a concentration of 1.0 M, and then 30.0 wt % of the compound represented by Formula 1 and other additives such as 1.0 wt % vinylene carbonate, 1.0 wt % 1,3-propane sultone, and 1.0 wt % ethylene sulfate were added to prepare a non-aqueous electrolyte.
[0096] (Secondary battery manufacturing) A pouch-type lithium secondary battery was manufactured in the same manner as in Example 1, except that the non-aqueous electrolyte prepared above was injected.
[0097] Comparative example. A nonaqueous electrolyte for a lithium secondary battery and a pouch-type lithium secondary battery containing the same were manufactured in the same manner as in Example 1, except that LiPF6 was dissolved to a concentration of 1.0 M in a nonaqueous organic solvent prepared by mixing ethylene carbonate (EC) and ethyl methyl carbonate (EMC) in a volume ratio of 30:70, and 1.0 wt % of vinylene carbonate, 1.0 wt % of 1,3-propane sultone, and 1.0 wt % of ethylene sulfate were added to prepare a nonaqueous electrolyte.
[0098] [Experimental Example] Experimental example 1. Evaluation of low-temperature output characteristics The lithium secondary batteries prepared in Examples 1 and 2 and the lithium secondary battery prepared in Comparative Example were each charged at a constant current of 0.04 C to 4.2 V at room temperature (25° C.), and then discharged to 3.0 V under constant current (CC) conditions. This cycle was considered as one cycle. The initial discharge capacities were then measured and shown in Table 1 below.
[0099] Next, the battery was charged to 10% SOC (state of charge) at a constant current of 0.04C and then stored at low temperature (-10°C) for 1 hour. The discharge capacity after 1 hour was calculated as a percentage based on the initial discharge capacity. The results are shown in Table 1 below.
[0100] [Table 1]
[0101] Referring to Table 1, it can be seen that the lithium secondary batteries of Examples 1 and 2 of the present invention have slightly lower initial capacities at room temperature than the lithium secondary battery of the Comparative Example, but have improved capacity retention rates after low-temperature storage than the lithium secondary battery of the Comparative Example.
[0102] Experimental Example 2: Evaluation of high-temperature storage characteristics The lithium secondary batteries prepared in Examples 1 and 2 and the lithium secondary battery prepared in Comparative Example were each charged at a constant current of 0.04 C to 4.2 V at room temperature (25° C.), and then discharged to 3.0 V under constant current (CC) conditions. Each cycle was one cycle. The initial discharge capacity was measured by performing three cycles.
[0103] Next, the battery was charged to 100% SOC (state of charge) at a constant current of 0.04C and then stored at high temperature (60°C) for 20 weeks, while measuring the thickness increase rate every 4 weeks. The results are shown in Figure 1.
[0104] Referring to FIG. 1, it can be seen that in the lithium secondary batteries of Examples 1 and 2 of the present invention, the amount of gas generated during high temperature storage is reduced, and thus the thickness increase rate is relatively reduced compared to the comparative example.
[0105] Experimental Example 3: Evaluation of high temperature stability characteristics The lithium secondary battery prepared in Example 3 and the lithium secondary battery prepared in Comparative Example were each charged at a constant current of 0.04 C to 4.2 V at room temperature (25° C.), and then discharged to 3.0 V under constant current (CC) conditions. This cycle was considered as one cycle. The initial discharge capacity was then measured.
[0106] Next, the battery was charged to 100% SOC (state of charge) at a constant current of 0.04 C, and then the amount of heat generated inside the battery was measured while the temperature was raised to a high temperature (300°C). The results are shown in Table 2 below.
[0107] [Table 2]
[0108] Referring to Table 2, it can be seen that the lithium secondary battery of Example 3 of the present invention has improved high temperature stability due to a reduction in the amount of heat generated at high temperatures compared to the lithium secondary battery of the Comparative Example.
Claims
1. A non-aqueous electrolyte for a lithium secondary battery comprising a lithium salt, a non-aqueous organic solvent, and an ionic liquid represented by the following chemical formula 1: 【Chemistry 1】 In the above Chemical Formula 1, R is an alkylene group having 1 to 5 carbon atoms; R 1 ~R 3 each independently represents an alkyl group having 1 to 8 carbon atoms or an aryl group having 6 to 12 carbon atoms, X - is BF 4 - , P.F. 6 - , ClO 4 - , P.O. 2 F 2 - , C.F. 3 SO 3 - , C.H. 3 CO 2 - , C.F. 3 CO 2 - , S.O. 3 CF 3 - , (CF 3 CF 2 SO 2 ) 2 N - , (CF 3 SO 2 ) 2 N - , (FSO 2 ) 2 N - , C.F. 3 CF 2 SO 3 - , C.F. 3 CF 2 (CF 3 ) 2 CO - , B(C 2 O 4 ) 2 - , and B.F. 2 (C 2 O 4 ) - and wherein the anion is at least one selected from the group consisting of:
2. R is an alkylene group having 1 to 3 carbon atoms, R 1 ~R 3 are each independently an alkyl group having 1 to 5 carbon atoms or a phenyl group, X - is BF 4 - , P.F. 6 - , ClO 4 - , P.O. 2 F 2 - , C.F. 3 SO 3 - , S.O. 3 CF 3 - , (CF 3 CF 2 SO 2 ) 2 N - , (CF 3 SO 2 ) 2 N - , (FSO 2 ) 2 N - , C.F. 3 CF 2 SO 3 - , C.F. 3 CF 2 (CF 3 ) 2 CO - , and B.F. 2 (C 2 O 4 ) - 2. The nonaqueous electrolyte for a lithium secondary battery according to claim 1, wherein the anion is at least one selected from the group consisting of:
3. The R 1 ~R 3 and each independently represent a methyl group, an ethyl group, or a phenyl group.
4. The nonaqueous electrolyte for a lithium secondary battery according to claim 1, wherein the ionic liquid represented by Chemical Formula 1 is at least one of compounds represented by the following Chemical Formulas 1-1 to 1-4. 【Chemistry 2】 【Chemistry 3】 【Chemistry 4】 【Chemistry 5】
5. 2. The non-aqueous electrolyte solution for a lithium secondary battery according to claim 1, wherein the ionic liquid represented by Formula 1 is contained in an amount of 0.3 wt % to 50 wt % based on the total weight of the non-aqueous electrolyte solution for a lithium secondary battery.
6. 6. The non-aqueous electrolyte solution for a lithium secondary battery according to claim 5, wherein the ionic liquid represented by Formula 1 is contained in an amount of 0.5 wt % to 30 wt % based on the total weight of the non-aqueous electrolyte solution for a lithium secondary battery.
7. 2. The nonaqueous electrolyte solution for a lithium secondary battery according to claim 1, further comprising at least one other additive selected from the group consisting of a cyclic carbonate-based compound, a halogen-substituted carbonate-based compound, a sultone-based compound, a sulfate-based compound, a phosphate-based or phosphite-based compound, a borate-based compound, a benzene-based compound, an amine-based compound, a silane-based compound, and a lithium salt-based compound.
8. A battery comprising a negative electrode, a positive electrode, a separator interposed between the negative electrode and the positive electrode, and a non-aqueous electrolyte; The nonaqueous electrolyte solution for lithium secondary batteries according to claim 1 .
Citation Information
Patent Citations
Nonaqueous electrolyte secondary battery and nonaqueous electrolyte
JP2006092748A